2004
DOI: 10.1088/0967-3334/25/1/038
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brain oedema using magnetic induction tomography: a feasibility study of the likely sensitivity and detectability

Abstract: The detection and continuous monitoring of brain oedema is of particular interest in clinical applications because existing methods (invasive measurement of the intracranial pressure) may cause considerable distress for the patients. A new non-invasive method for continuous monitoring of an oedema promises the use of multi-frequency magnetic induction tomography (MIT). MIT is an imaging method for reconstructing the changes of the conductivity deltakappa in a target object. The sensitivity of a single MIT-chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…The brain region was assumed to consist of homogeneous isotropic grey matter. The conductivity of cerebrospinal fluid was taken to be 1.6 S m -1 [20], and its relative permittivity to be 200 [21]. Material properties were spatially invariant within each region.…”
Section: A Materials Propertiesmentioning
confidence: 99%
“…The brain region was assumed to consist of homogeneous isotropic grey matter. The conductivity of cerebrospinal fluid was taken to be 1.6 S m -1 [20], and its relative permittivity to be 200 [21]. Material properties were spatially invariant within each region.…”
Section: A Materials Propertiesmentioning
confidence: 99%
“…Finally, the complete 10-tissue head model can be exported as a sat file. The head model volume is about 3900 cm 3 , with a resolution of 1 mm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The first report of applying an anatomically realistic model in the MIM simulation was by Merwa et al [3] They used 150 human head images from the Visible Man Human Project database and processed them with a custom-made software. The complete model incorporates brain white matter, brain grey matter, third ventricle, and lateral ventricle as structures.…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, Magnetic Induction Tomography (MIT) has been exploited for producing conductivity maps of the passive electromagnetic properties of an object. [3][4][5][6][7][8][9][10] In the context of nuclear security applications, Darrer et al 1,2 demonstrated an MIT-based imaging method that allows imaging of metals concealed inside ferromagnetic enclosures. Penetrating imaging, i.e.…”
Section: Introductionmentioning
confidence: 99%